Drishya: Object Detection And MonocuLar Depth Estimation Using Deep Learning - Tripathee, Saman; Aryal, Samyam; Bibash, Samiran Pratap (Journal of Advanced College of Engineering and Management, 2023)
This project focuses on object detection and depth estimation using computer vision. The aim of this project is to develop an accurate and reliable system for detecting objects and estimating their distances from a camera. The system uses deep learning-based algorithms to detect objects and estimate their distances. The results of the project show that the system can accurately detect objects and estimate their distances in some scenarios. This project presents an Android app for real-time object detection and depth estimation using computer vision with YOLOv5 and U-Net architecture.